2015
DOI: 10.1016/j.scs.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Qatar 2022: Facing the FIFA World Cup climatic and legacy challenges

Abstract: The 2022 World Cup creates great opportunities for the country of Qatar, but also poses significant challenges. In this study the main challenge of maintaining thermal comfort conditions within the football arenas is presented, with respect to the heat stress index (HSI) and the aero-thermal comfort thresholds established for opened stadiums. Potential cooling strategies for delivering tolerant comfort levels are introduced, followed by their functional strengths and limitations for the hot-humid climate of Qa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 33 publications
0
44
0
2
Order By: Relevance
“…The interactions between the urban environment and the stadium structures as well as the wind comfort conditions on pedestrian level have also attracted great interest [10][11][12]. Finally, thermal comfort studies, employing dynamic thermal modelling and CFD techniques, were also conducted to assess thermal discomfort and temperature distribution on stadia [2,[13][14][15]41] and energy consumption requirements [16,17,42].…”
Section: Previous Related Workmentioning
confidence: 99%
“…The interactions between the urban environment and the stadium structures as well as the wind comfort conditions on pedestrian level have also attracted great interest [10][11][12]. Finally, thermal comfort studies, employing dynamic thermal modelling and CFD techniques, were also conducted to assess thermal discomfort and temperature distribution on stadia [2,[13][14][15]41] and energy consumption requirements [16,17,42].…”
Section: Previous Related Workmentioning
confidence: 99%
“…Energy consumption for the buildings sector worldwide is expected to grow by 45% in the 2002-2025 period [4]. In rapidly developing Middle Eastern countries such as UAE and Qatar, air-conditioning (AC) is a key contributor to greenhouse gas (GHG) emissions [5]. The extreme conditions of local climate, affordable energy and increased demand for high-levels of comfort had led to the use of energy-intensive AC in nearly all buildings [5].…”
Section: Introductionmentioning
confidence: 99%
“…In rapidly developing Middle Eastern countries such as UAE and Qatar, air-conditioning (AC) is a key contributor to greenhouse gas (GHG) emissions [5]. The extreme conditions of local climate, affordable energy and increased demand for high-levels of comfort had led to the use of energy-intensive AC in nearly all buildings [5]. A study in 2005 [6] indicated that the average consumption per person in Gulf countries was almost 4 times higher than global average.…”
Section: Introductionmentioning
confidence: 99%
“…In hot climates, such as those in Middle East countries, the percentage of energy consumption by air conditioning (AC) is significantly larger due to the more extreme conditions of the local climate [3]. In 2005, the average Watt/person in the Gulf Cooperation Council (GCC) countries was 1149 Watt/person which was much greater than the world average (297 Watt/person) [4].…”
Section: Introductionmentioning
confidence: 99%